2019
DOI: 10.3233/bd-180351
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM-AS1 up-regulation in invasive ductal carcinoma of breast and assessment of its potential as a diagnostic biomarker

Abstract: BACKGROUND:The long non-coding RNA (lncRNA) DSCAM-AS1 has been demonstrated to participate in the pathogenesis of breast cancer and tamoxifen resistance. OBJECTIVE: To evaluate expression profile of DSCAM-AS1 in invasive ductal carcinoma of breast and its suitability as a biomarker for diagnosis of breast cancer. METHODS: We evaluated expression of DSCAM-AS1 in 108 breast tissues including tumoral and adjacent non-cancerous tissues (ANCTs) by means of quantitative real time PCR. RESULTS: DSCAM-AS1 was up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The role of DSCAM-AS1 has also been investigated in several studies. It is con rmed that DSCAM-AS1 expression was upregulated in breast cancer [23]; DSCAM-AS1 can target miR-137 and EPS8 to facilitate the proliferation of breast cancer cells while arrest their apoptosis, and DSCAM-AS1 can enhance the drug resistance of tamoxifen [24]. The above researches uncovered that DSCAM-AS1 had the function as an oncogene.…”
Section: Discussionmentioning
confidence: 92%
“…The role of DSCAM-AS1 has also been investigated in several studies. It is con rmed that DSCAM-AS1 expression was upregulated in breast cancer [23]; DSCAM-AS1 can target miR-137 and EPS8 to facilitate the proliferation of breast cancer cells while arrest their apoptosis, and DSCAM-AS1 can enhance the drug resistance of tamoxifen [24]. The above researches uncovered that DSCAM-AS1 had the function as an oncogene.…”
Section: Discussionmentioning
confidence: 92%
“…In recent decades, evidence has highlighted that the dysregulation of lncRNAs on CRC could be a leading cause for tumor process [8,9]. Studies show that DSCAM-AS1 has a role in progression of several cancers, and that it can function as an oncogenic lncRNA in these cancers [10][11][12][13][14][15][16]. Although recently studies demonstrated that DSCAM-AS1 expression was upregulated and played a crucial role in CRC, the functional roles and underlying mechanism of DSCAM-AS1 in CRC cells remains largely unknown [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Many lncRNAs are verified to play tumor suppressor or oncogenic role in the progression of CRC [8,9], suggesting that lncRNAs could serve as a diagnosis marker and therapy agent. Down Syndrome Cell Adhesion Molecule (DSCAM) antisense (DSCAM-AS1), (DSCAM-AS1), a novel lncRNA, has been reported to be upregulated and function as oncogenic lncRNA in hepatocellular carcinoma [10], non-small lung cancer [11], ovarian cancer [12], melanoma [13] and breast cancer [14][15][16]. Despite recently studies demonstrated that DSCAM-AS1 expression was upregulated in CRC and was involved in CRC proliferation and invasion [17,18], the function and underlying mechanism of DSCAM-AS1 in CRC progression remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of sensitive biomarkers for prognosis and diagnosis and novel therapeutic targets has a very essential clinical significance for the improvement of long-term survival of CRC. In recent years, growing evidence has suggested that lncRNAs are tightly linked to the initiation and development of human cancers [13,14,20,23]. Previous studies have suggested the vital role of DSCAM-AS1 in hepatocellular carcinoma [24], breast cancer [20] and ovarian cancer [15].…”
Section: Discussionmentioning
confidence: 99%